Atomic force microscopy characterization of an electrochemical DNA-biosensor - Paquim, Ana Maria Chiorcea (2004)
Electrode surface characteristics represent an important aspect on the construction of sensitive DNA electrochemical biosensors for rapid detection of DNA interaction and damage. Two different immobilization procedures of double-stranded DNA (dsDNA) at the surface of a HOPG electrode were evaluated by MAC mode AFM performed in air. A thin dsDNA adsorbed film forming a network structure with holes exposing the electrode surface and a thick dsDNA film completely covering the electrode surface, presenting a much rougher structure, were investigated. The DNA surface characteristics and structure are discussed with respect to the degree of surface coverage.